Alternatives to Animal Use in Risk Assessment of Mixtures. (March 2020) - Wallace Hayes, A.; Muriana, Arantza; Alzualde, Ainhoa; Fernandez, Dania Bacardi; Iskandar, Anita; Peitsch, Manuel C.; Kuczaj, Arkadiusz; Hoeng, Julia
Risk assessment of chemical mixtures has emerged as a focus of research efforts, but traditional toxicology testing in mammals is costly, time-consuming, and subject to ethical scrutiny in the context of recent trends to reduce reliance on animal testing. In this review, which is a summary of presentations given at a workshop in Havana, Cuba, in April 2019, we survey the utility of zebra fish as an alternative laboratory model in whole-mixture and component-based testing, as well as in vitro modeling in 3-dimensional organotypic cultures from primary human cells cultured at the air–liquid interface and organ-on-a-chip platforms. Finally, we discuss the complexities of assessing the dynamics and delivery of multispecies liquid aerosol mixtures along the human respiratory tract, with examples of alternative and computational approaches to aerosol dosimetry. The workshop contributed to the professional development of Cuban toxicologists, an underserved segment of the global scientific community, delivering a set of tools and recommendations that could potentially provide cost-effective solutions for scientists with limited research resources.